Bulletproof aramid polyurea composite material based on ultraviolet modification and preparation method thereof
Through the combination of ultraviolet modification treatment and polyurea coating, the problems of poor adhesion and insufficient bulletproof performance of aramid fiber are solved, bulletproof performance and human-machine efficacy performance are improved, and softness and breathability are improved.
Patent Information
- Application Number
- CN202410843111.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-06-27
AI Technical Summary
The surface chemical inertia and smoothness of traditional aramid fibers lead to poor adhesion with the matrix material, insufficient flame retardant and bulletproof performance, and the polyurea material has high hardness, poor softness and poor breathability, making it difficult to meet actual needs.
The surface roughness of aramid fiber is increased by ultraviolet modification treatment, and combined with materials such as aldehyde-based compounds and isocyanate compounds to prepare a polyurea coating to enhance the adhesion of aramid fiber to polyurea and the impact resistance of the composite material.
It significantly improves the bulletproof performance, flexibility and breathability of aramid fiber and polyurea composite materials, improves the human-machine efficacy performance, and enhances the impact resistance of the composite materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber fabric modification, in particular to a bulletproof aramid polyurea composite material based on ultraviolet modification and a preparation method thereof. Background Art
[0002] Aramid fiber has the advantages of high strength, high modulus, heat resistance, corrosion resistance, etc. It has excellent strength and deformation characteristics and has good application prospects in safety protection engineering fields such as explosion-proof, earthquake-resistant, and impact-resistant. Due to the high crystallinity of the aramid fiber surface and the lack of polar functional groups in the macromolecular chain, the surface is chemically inert and smooth, resulting in poor adhesion to the matrix material, so the aramid fiber needs to be treated to improve the adhesion between the aramid fiber and the matrix material.
[0003] The purpose of aramid fiber modification is to improve the surface chemical activity of the fiber and increase the surface roughness so as to achieve good chemical bonding and mechanical interlocking between the aramid fiber and the matrix material. Ultraviolet irradiation is a physical modification method. Through the irradiation of rays, the number of active groups on the surface of the aramid fiber increases, and the surface roughness increases, which increases the surface energy. In addition, it is one of the effective ways to increase the anti-ballistic performance of aramid fibers due to its fast reaction speed, low operating cost and simple equipment. Traditional aramid materials have poor flame retardancy and the anti-ballistic performance is difficult to meet actual needs. In addition, traditional polyurea materials have problems such as high hardness, poor softness, and poor air permeability, which lead to poor comfort.
[0004] The Chinese patent application number 201910295485.4 discloses a meta-aramid fabric with surface functional modification. The meta-aramid fabric is treated with a modified liquid composed of a mixture of N, N-dimethylacetamide, LiCl, and inorganic functional nanoparticles, so that the macromolecules on the fiber surface react with N, N-dimethylacetamide and LiCl to form a slightly soluble layer. The inorganic functional nanoparticles on the fiber surface are squeezed into the slightly soluble layer under the action of positive pressure. Then, under high temperature and negative pressure conditions, the N, N-dimethylacetamide in the slightly soluble layer is volatilized and extracted, and the inorganic functional nanoparticles are solidified on the surface of the meta-aramid fiber, which enhances the flame retardant, antistatic, radiation resistance and other functions of the meta-aramid surface.
[0005] The Chinese patent application with application number 202310241904.2 discloses a method for protecting bulletproof fiber fabrics in harsh environments based on copper-silver oxide modification. By modifying the fiber fabric, the impact resistance of the fiber fabric is increased, and the protective effect of the fiber fabric against projectiles is effectively improved. After the fiber fabric is pre-treated by acid washing, alkali washing and other pretreatments to remove surface impurities, it is immersed in an ethanol solution of vinyl acetic acid to improve its surface properties, then immersed in a copper oxide impregnation solution to generate copper hydroxides, and then immersed in a silver oxide impregnation solution to generate silver hydroxides on its surface, and finally a composite oxide layer of copper oxide and silver oxide is formed, which can significantly enhance its resistance to harsh environments of humidity, heat and strong ultraviolet rays, so that the anti-ballistic properties of the fiber fabric can be maintained for a long time.
[0006] The Chinese patent application number 202111365292.5 discloses a polyurea-metal-polyurea composite structure and preparation method for improving bulletproof and explosion-proof performance. A 3mm bulletproof polyurea layer is sprayed on one side of the metal plate, and a 5mm-15mm explosion-proof polyurea layer is sprayed on the other side. The hardening, strengthening and interface failure of the polyurea elastomer under strong impact enhance the bulletproof and explosion-proof performance of the polyurea-metal composite structure, so as to achieve the maximum comprehensive bulletproof and explosion-proof performance with the original protective material / structure, making a significant contribution to the field of lightweight protection. Summary of the invention
[0007] In view of the defects of the prior art, the present invention provides a bulletproof aramid polyurea composite material based on UV modification and a preparation method thereof, which enables the aramid fiber and the polyurea coating to have a better connection, increases the impact resistance of the composite material, and improves the bulletproof performance of the composite material fabric.
[0008] The specific technical scheme is a method for preparing a bulletproof aramid polyurea composite material based on ultraviolet modification, comprising the steps of:
[0009] S1, fiber pretreatment, remove impurities on the aramid surface,
[0010] S2, UV-modified aramid, increasing surface roughness,
[0011] S3, the preparation of polyurea coating comprises the following steps:
[0012] S31, stirring the aldehyde compound and the thiol compound in an aqueous solvent until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor,
[0013] S32, stirring the isocyanate compound and the amino compound in an aqueous solvent until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor,
[0014] S33, mixing the solutions obtained in step S31 and step S32, stirring and reacting for 2-3 hours, and curing in a drying oven at 80-88° C. for 24-36 hours to obtain a polyurea coating material,
[0015] S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, to obtain an aramid polyurea composite material fabric.
[0016] Preferably, step S2 comprises the steps of:
[0017] S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator,
[0018] S22, adding 2.5%-20% by mass of glycidyl methacrylate to the photoinitiator solution,
[0019] S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 5-10 minutes to eliminate oxygen, and irradiating the solution with 300-400mm ultraviolet rays for 10-30 minutes under a 500V high-pressure mercury lamp at room temperature,
[0020] S24. Take out the aramid fiber obtained in step S23, wash it with ethanol and distilled water for more than three times to remove physically absorbed monomers or homopolymers, and dry it in a vacuum oven for 10-13 hours at an oven temperature of 90-100°C.
[0021] Preferably, the mass fraction of the photoinitiator prepared in step S21 is 2.5%.
[0022] Preferably, the ultraviolet irradiation time in step S23 is 15 minutes.
[0023] Preferably, the drying time in step S24 is 12 hours.
[0024] Preferably, in step S31, the mass ratio of the aldehyde compound to the thiol compound is 1:1.2-1.5; in step S32, the mass ratio of the isocyanate compound to the amino compound is 1:3.2-3.7.
[0025] Preferably, in step S31, the aldehyde compound is trialdehyde pyrogallol, and the thiol compound is bis(3-mercaptopropionate) glycol, with a mass ratio of 1:1.4; in step S33, the isocyanate compound is xylene diisocyanate, and the amino compound is amino-terminated polytetrahydrofuran, with a mass ratio of 1:3.6.
[0026] Preferably, step S1 comprises the steps of:
[0027] S11, placing the aramid fiber in anhydrous ethanol solution for ultrasonic cleaning for 20-30 minutes, the ultrasonic temperature is 20-30°C, and the surface oil stains and impurities are removed by ultrasonic immersion.
[0028] S12, placing the cleaned aramid fiber in a vacuum oven and drying it for 4-6 hours at a vacuum drying temperature of 90-100°C.
[0029] Preferably, the concentration of the anhydrous ethanol solution used in step S11 is 99.5%.
[0030] Aramid polyurea composite material fabric is prepared based on an ultraviolet-modified bulletproof aramid polyurea composite material and the preparation method is adopted.
[0031] Compared with the prior art, the invention promotes the grafting of glycidyl methacrylate on the surface of aramid fiber by ultraviolet irradiation, so that the surface of aramid fiber becomes rougher, and epoxy groups are introduced into the surface of aramid fiber to improve the adhesion with polyurea, so that it can be better combined with polyurea coating, increase the impact resistance of aramid polyurea composite material, improve the anti-ballistic performance of composite material fabric, and at the same time, the softness and air permeability of aramid polyurea composite material fabric are also improved, and the comfort is improved; glycidyl methacrylate with a mass fraction of 10%-20% can significantly improve the anti-ballistic performance of fabric, and the obtained aramid polyurea composite material fabric can improve the ergonomic performance to the greatest extent while ensuring the anti-ballistic performance. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Here, the illustrative embodiments of the present invention and their descriptions are used to explain the present invention, but are not intended to limit the present invention.
[0033] The preparation method of the bulletproof aramid polyurea composite material based on ultraviolet modification comprises the following steps:
[0034] S1, fiber pretreatment, remove impurities on the aramid surface,
[0035] S2, UV-modified aramid, increasing surface roughness,
[0036] S3, the preparation of polyurea coating comprises the following steps:
[0037] S31, stirring the aldehyde compound and the thiol compound in an aqueous solvent until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor,
[0038] S32, stirring the isocyanate compound and the amino compound in an aqueous solvent until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor,
[0039] S33, mixing the solutions obtained in step S31 and step S32, stirring and reacting for 2-3 hours, and curing in a drying oven at 80-88° C. for 24-36 hours to obtain a polyurea coating material,
[0040] S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, to obtain an aramid polyurea composite material fabric.
[0041] In one embodiment, step S2 comprises the steps of:
[0042] S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator,
[0043] S22, adding 2.5%-20% by mass of glycidyl methacrylate to the photoinitiator solution,
[0044] S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 5-10 minutes to eliminate oxygen, and irradiating the solution with 300-400mm ultraviolet rays for 10-30 minutes under a 500V high-pressure mercury lamp at room temperature,
[0045] S24. Take out the aramid fiber obtained in step S23, wash it with ethanol and distilled water for more than three times to remove physically absorbed monomers or homopolymers, and dry it in a vacuum oven for 10-13 hours at an oven temperature of 90-100°C.
[0046] In one embodiment, the mass fraction of the photoinitiator prepared in step S21 is 2.5%.
[0047] In one embodiment, the ultraviolet irradiation duration in step S23 is 15 minutes.
[0048] In one embodiment, the drying time in step S24 is 12 hours.
[0049] In one embodiment, in step S31, the mass ratio of the aldehyde compound to the thiol compound is 1:1.2-1.5; in step S32, the mass ratio of the isocyanate compound to the amino compound is 1:3.2-3.7.
[0050] In one embodiment, in step S31, the aldehyde compound is trialdehyde pyrogallol, and the thiol compound is bis(3-mercaptopropionate) glycol, and the mass ratio is 1:1.4; in step S33, the isocyanate compound is xylene diisocyanate, and the amino compound is amino-terminated polytetrahydrofuran, and the mass ratio is 1:3.6.
[0051] In one embodiment, step S1 comprises the steps of:
[0052] S11, placing the aramid fiber in anhydrous ethanol solution for ultrasonic cleaning for 20-30 minutes, the ultrasonic temperature is 20-30°C, and the surface oil stains and impurities are removed by ultrasonic immersion.
[0053] S12, placing the cleaned aramid fiber in a vacuum oven and drying it for 4-6 hours at a vacuum drying temperature of 90-100°C.
[0054] In one embodiment, the concentration of the anhydrous ethanol solution used in step S11 is 99.5%.
[0055] Aramid polyurea composite material fabric is prepared based on an ultraviolet-modified bulletproof aramid polyurea composite material and the preparation method is adopted.
[0056] Example 1: Based on the ultraviolet modified bulletproof aramid polyurea composite material, the preparation steps are as follows:
[0057] S1, fiber pretreatment, removing impurities on the aramid surface, step S1 includes the following steps:
[0058] S11, placing the aramid fiber in anhydrous ethanol solution for ultrasonic cleaning for 20 minutes, the ultrasonic temperature is 20°C, and the surface oil stains and impurities are removed by ultrasonic immersion.
[0059] S12, placing the cleaned aramid fiber in a vacuum oven and drying it for 4 hours at a vacuum drying temperature of 90°C.
[0060] S2, ultraviolet light modifies aramid to increase surface roughness, step S2 comprises the following steps:
[0061] S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator,
[0062] S22, adding 2.5% by mass of glycidyl methacrylate to the photoinitiator solution,
[0063] S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 5 minutes to eliminate oxygen, and irradiating the solution with 300-400mm ultraviolet rays for 10 minutes under a 500V high-pressure mercury lamp at room temperature.
[0064] S24, taking out the aramid fiber obtained in step S23, washing it with ethanol and distilled water for more than three times to remove physically absorbed monomers or homopolymers, and drying it in a vacuum oven at 90° C. for 13 h.
[0065] S3, the preparation of polyurea coating comprises the following steps:
[0066] S31, stirring an aldehyde compound and a thiol compound in a water solvent at a mass ratio of 1:1.2 until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor,
[0067] S32, stirring the isocyanate compound and the amino compound in a water solvent at a mass ratio of 1:3.2 until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor,
[0068] S33, mixing the solutions obtained in step S31 and step S32 with each other, with the mass ratio of the solvent to the mixed substance being 1:1-2, stirring for reaction for 3 hours, and curing in a drying oven at 80° C. for 36 hours to obtain a polyurea coating material,
[0069] S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, wherein the sample surface density gain does not exceed 10%, to obtain an aramid polyurea composite material fabric.
[0070] The sprayed aramid fabric was characterized. Compared with the traditional aramid material fabric directly sprayed with polyurea, the ballistic limit velocity of the modified polyurea aramid composite fabric increased by 9.8%, the softness increased by 2.2%, and the air permeability increased by 9.3%.
[0071] Example 2: Based on the ultraviolet modified bulletproof aramid polyurea composite material, the preparation steps are as follows:
[0072] S1, fiber pretreatment, removing impurities on the aramid surface, step S1 includes the following steps:
[0073] S11, placing the 1414 aramid fiber in a 99.5% anhydrous ethanol solution for ultrasonic cleaning for 30 minutes, the ultrasonic temperature is 25°C, and the surface oil stains and impurities are removed by ultrasonic immersion.
[0074] S12. Place the cleaned aramid fiber in a vacuum oven and dry it for 6 hours at a vacuum drying temperature of 95°C. The anhydrous ethanol will vaporize at high temperature and will not affect the subsequent experimental structure.
[0075] S2, ultraviolet light modifies aramid to increase surface roughness, step S2 comprises the following steps:
[0076] S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator with a mass fraction of 2.5%,
[0077] S22, adding 5% by mass of glycidyl methacrylate to the photoinitiator solution,
[0078] S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 10 minutes to eliminate oxygen, and irradiating the solution with 300-400mm ultraviolet rays for 20 minutes under a 500V high-pressure mercury lamp at room temperature.
[0079] S24, taking out the aramid fiber obtained in step S23, washing it with ethanol and distilled water for more than three times to remove physically absorbed monomers or homopolymers, and drying it in a vacuum oven at a temperature of 100° C. for 12 hours.
[0080] S3, the preparation of polyurea coating comprises the following steps:
[0081] S31, stirring trialdehyde phloroglucinol and bis(3-mercaptopropionate)ethylene glycol in a mass ratio of 1:1.5 in an aqueous solvent until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor,
[0082] S32, stirring xylylene diisocyanate and amino-terminated polytetrahydrofuran in a water solvent at a mass ratio of 1:3.7 until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor,
[0083] S33, mixing the solutions obtained in step S31 and step S32 with each other, with the mass ratio of the solvent to the mixed substance being 1:1-2, stirring for reaction for 2 hours, and curing in a drying oven at 88° C. for 30 hours to obtain a polyurea coating material,
[0084] S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, wherein the sample surface density gain does not exceed 10%, to obtain an aramid polyurea composite material fabric.
[0085] The modified aramid fabric was characterized and found to have a rougher surface, which could better bond with the polyurea coating. Compared with the traditional aramid fabric directly sprayed with polyurea, the ballistic limit velocity of the modified polyurea aramid composite fabric increased by 20.6%, the softness increased by 2.2%, and the air permeability increased by 8.1%.
[0086] Example 3: Based on the ultraviolet modified bulletproof aramid polyurea composite material, the preparation steps are as follows:
[0087] S1, fiber pretreatment, removing impurities on the aramid surface, step S1 includes the following steps:
[0088] S11, placing the 1414 aramid fiber in a 99.5% anhydrous ethanol solution for ultrasonic cleaning for 25 minutes, the ultrasonic temperature is 30°C, and the surface oil stains and impurities are removed by ultrasonic immersion.
[0089] S12. Place the cleaned aramid fiber in a vacuum oven and dry it for 5 hours at a vacuum drying temperature of 100°C. Anhydrous ethanol will vaporize at high temperature and will not affect the subsequent experimental structure.
[0090] S2, ultraviolet light modifies aramid to increase surface roughness, step S2 comprises the following steps:
[0091] S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator with a mass fraction of 2.5%,
[0092] S22, adding 15% by mass of glycidyl methacrylate to the photoinitiator solution,
[0093] S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 5 minutes to eliminate oxygen, and irradiating the solution with 300-400mm ultraviolet rays for 25 minutes under a 500V high-pressure mercury lamp at room temperature,
[0094] S24, taking out the aramid fiber obtained in step S23, washing it with ethanol and distilled water for more than three times to remove physically absorbed monomers or homopolymers, and drying it in a vacuum oven at a temperature of 100° C. for 10 hours.
[0095] S3, the preparation of polyurea coating comprises the following steps:
[0096] S31, stirring trialdehyde phloroglucinol and bis(3-mercaptopropionate)ethylene glycol in a mass ratio of 1:1.4 in an aqueous solvent until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor,
[0097] S32, stirring xylylene diisocyanate and amino-terminated polytetrahydrofuran in a water solvent at a mass ratio of 1:3.6 until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor,
[0098] S33, mixing the solutions obtained in step S31 and step S32 with each other, with the mass ratio of the solvent to the mixed substance being 1:1-2, stirring for reaction for 2 hours, and curing in a drying oven at 85° C. for 24 hours to obtain a polyurea coating material,
[0099] S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, wherein the sample surface density gain does not exceed 10%, to obtain an aramid polyurea composite material fabric.
[0100] The modified aramid fabric was characterized and found to have a rougher surface, which could better bond with the polyurea coating. Compared with the traditional aramid fabric directly sprayed with polyurea, the ballistic limit velocity of the modified polyurea aramid composite fabric increased by 26.3%, the softness increased by 1.1%, and the air permeability increased by 6.2%.
[0101] Example 4: Based on the ultraviolet modified bulletproof aramid polyurea composite material, the preparation steps are as follows:
[0102] S1, fiber pretreatment, removing impurities on the aramid surface, step S1 includes the following steps:
[0103] S11, placing the 1414 aramid fiber in a 99.5% anhydrous ethanol solution for ultrasonic cleaning for 30 minutes, the ultrasonic temperature is 25°C, and the surface oil stains and impurities are removed by ultrasonic immersion.
[0104] S12. Place the cleaned aramid fiber in a vacuum oven and dry it for 6 hours at a vacuum drying temperature of 95°C. The anhydrous ethanol will vaporize at high temperature and will not affect the subsequent experimental structure.
[0105] S2, ultraviolet light modifies aramid to increase surface roughness, step S2 comprises the following steps:
[0106] S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator with a mass fraction of 2.5%,
[0107] S22, adding 20% by mass of glycidyl methacrylate to the photoinitiator solution,
[0108] S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 5 minutes to eliminate oxygen, and irradiating the solution with 300-400mm ultraviolet rays for 30 minutes under a 500V high-pressure mercury lamp at room temperature,
[0109] S24, taking out the aramid fiber obtained in step S23, washing it with ethanol and distilled water for more than three times to remove physically absorbed monomers or homopolymers, and drying it in a vacuum oven at 95° C. for 10 h.
[0110] S3, the preparation of polyurea coating comprises the following steps:
[0111] S31, stirring trialdehyde phloroglucinol and bis(3-mercaptopropionate)ethylene glycol in a mass ratio of 1:1.4 in an aqueous solvent until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor,
[0112] S32, stirring xylylene diisocyanate and amino-terminated polytetrahydrofuran in a water solvent at a mass ratio of 1:3.6 until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor,
[0113] S33, mixing the solutions obtained in step S31 and step S32 with each other, with the mass ratio of the solvent to the mixed substance being 1:1-2, stirring for reaction for 2 hours, and curing in a drying oven at 85° C. for 24 hours to obtain a polyurea coating material,
[0114] S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, wherein the sample surface density gain does not exceed 10%, to obtain an aramid polyurea composite material fabric.
[0115] The modified aramid fabric was characterized and found to have a rougher surface, which could better bond with the polyurea coating. Compared with the traditional aramid fabric directly sprayed with polyurea, the ballistic limit velocity of the modified polyurea aramid composite fabric increased by 36.2%, the softness increased by 1.1%, and the air permeability increased by 5.0%.
[0116] Comparative Example: The steps for preparing aramid polyurea composite fabric are as follows:
[0117] S1. Place the aramid fiber in an ethanol solution for ultrasonic cleaning for 30 minutes.
[0118] S2. Place the cleaned aramid fiber in a vacuum oven and dry for 6 hours.
[0119] S3, mixing isocyanate and amino-terminated polyether in a ratio of 1.1:1, and drying and curing at room temperature for 72 hours to form a polyurea coating material,
[0120] S4. Spray the polyurea coating material obtained in step S3 onto the aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, wherein the sample surface density gain does not exceed 10%, to obtain an aramid polyurea composite material fabric.
[0121] The ballistic limit velocity, softness and air permeability of Examples 1-4 and the comparative example were tested. The results are shown in Table 1.
[0122] Description of ballistic limit speed, softness and breathability:
[0123] The ballistic limit test method of fiber fabrics: a high-pressure ballistic impact device is used for testing. The bullet used for ballistic impact is a spherical steel ball with a diameter of 5mm. The power of the bullet mainly comes from the high-pressure gas in the gas storage chamber. The high-pressure gas pressure is changed to obtain a bullet incident speed of 40-300m / s. The experiment uses a high-speed photography equipment to mainly record and measure the instantaneous speed before and after the bullet impact, and calculate the ballistic limit speed V of the experimental sample based on the incident speed and residual speed. 50 The target plate has an external dimension of 18×18 cm and an internal window dimension of 16×16 cm. It is fixed at four corners and a stainless steel frame is selected to clamp the four corners of the sample.
[0124] Fiber fabric softness test: A narrow fiber fabric sample of a certain size is used as a cantilever beam. Based on its flexibility, its bending length, bending stiffness and bending modulus can be tested and calculated as an indicator of fabric softness. The larger the bending length value, the stiffer the fabric is and the harder it is to bend.
[0125] Fiber fabric air permeability test: Using the differential pressure test principle, place the pre-treated sample between the upper and lower test chambers and clamp them. First, vacuum the low-pressure chamber, i.e. the lower chamber, and then evacuate the entire system. When the specified vacuum degree is reached, close the lower chamber and fill the high-pressure chamber with a certain pressure of test gas, and ensure that a constant pressure is formed on both sides of the sample, so as to obtain the various barrier parameters of the tested sample.
[0126] By comparing Examples 1-4 with the comparative example, it can be found that as the concentration of the modified raw material increases, the modified aramid fiber fabric can better combine with the polyurea coating to form a new polyurea aramid composite fabric, which can greatly improve the impact resistance and anti-ballistic performance of the fabric. The softness test using the drape method found that the softness of Examples 1-4 was slightly improved compared with the comparative example; according to the GB / T5453-1997 air permeability test, it was found that the air permeability was effectively improved compared with the comparative example.
[0127] Table 1. Table of test performance results of Examples 1-4 and Comparative Examples
[0128]
[0129] The above is only the preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a bulletproof aramid polyurea composite material modified by ultraviolet light, characterized in that: Includes steps: S1, fiber pretreatment, remove impurities on the aramid surface, S2, UV-modified aramid, increasing surface roughness, S3, the preparation of polyurea coating comprises the following steps: S31, stirring the aldehyde compound and the thiol compound in an aqueous solvent until the viscosity no longer increases, to obtain an aldehyde-terminated polysemithioacetal precursor, S32, stirring the isocyanate compound and the amino compound in an aqueous solvent until the viscosity no longer increases, to obtain an amino-terminated polyurea precursor, S33, mixing the solutions obtained in step S31 and step S32, stirring and reacting for 2-3 hours, and curing in a drying oven at 80-88° C. for 24-36 hours to obtain a polyurea coating material, S4, spraying the polyurea coating material obtained in step S3 onto the modified aramid fiber material obtained in step S2, with a spraying thickness of 1.5-2 mm, to obtain an aramid polyurea composite material fabric.
2. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 1, characterized in that: Step S2 comprises the steps of: S21, using acetone as solvent and benzophenone as solute to prepare a photoinitiator, S22, adding 2.5%-20% by mass of glycidyl methacrylate to the photoinitiator solution, S23, immersing the aramid fiber in the mixed solution obtained in step S22, and purging the solution with pure nitrogen for 5-10 minutes, and irradiating the solution with 300-400mm ultraviolet rays for 10-30 minutes under a 500V high-pressure mercury lamp at room temperature, S24. Take out the aramid fiber obtained in step S23, wash it with ethanol and distilled water for more than three times, and dry it in a vacuum oven for 10-13 hours at a temperature of 90-100°C.
3. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 2, characterized in that: The mass fraction of the photoinitiator prepared in step S21 is 2.5%.
4. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 2, characterized in that: The ultraviolet irradiation time in step S23 is 15 minutes.
5. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 2, characterized in that: The drying time in step S24 is 12 hours.
6. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 1, characterized in that: In step S31, the mass ratio of the aldehyde compound to the thiol compound is 1:1.2-1.5; in step S32, the mass ratio of the isocyanate compound to the amino compound is 1:3.2-3.
7.
7. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 1, characterized in that: In step S31, the aldehyde compound is trialdehyde pyrogallol, and the thiol compound is bis(3-mercaptopropionate) glycol, with a mass ratio of 1:1.4; in step S33, the isocyanate compound is xylene diisocyanate, and the amino compound is amino-terminated polytetrahydrofuran, with a mass ratio of 1:3.
6.
8. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to any one of claims 1 to 7, characterized in that: Step S1 includes the steps of: S11, place the aramid fiber in anhydrous ethanol solution for ultrasonic cleaning for 20-30 minutes, the ultrasonic temperature is 20-30°C, S12, placing the cleaned aramid fiber in a vacuum oven and drying it for 4-6 hours at a vacuum drying temperature of 90-100°C.
9. The method for preparing the ultraviolet-modified bulletproof aramid polyurea composite material according to claim 8, characterized in that: The concentration of the anhydrous ethanol solution used in step S11 is 99.5%.
10. A bulletproof aramid polyurea composite material based on UV modification, characterized in that: Aramid polyurea composite fabric prepared by the preparation method described in claims 1-9.
Citation Information
Patent Citations
Method for surface function modification of meta-aramid fabric
CN110130101A
Polyurea-metal-polyurea composite structure capable of improving bulletproof and explosion-proof performance and preparation method
CN114210529A
Method for modifying and protecting bulletproof fiber fabric in severe environment based on copper-silver oxide
CN116716723A
Anti-explosion impact polyurea coating and preparation method thereof
CN106753151A
Kelvar fiber cloth-reinforced polyurea-based composite material and preparation method thereof
CN107011648A
Cited By
Bulletproof composite material and preparation method thereof
CN120623722A
